Informasi Sebaran Titik Panas Berbasis WebGIS untuk Pemantauan Kebakaran Hutan dan Lahan di Indonesia - Hidayat, Taufik; Priyatna, Muhammad; Sutanto, Ahmad; Alkhudri, Aby; Khomarudin, Rokhis (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTThe Remote Sensing Application Center Ã¢â‚¬â€œ LAPAN has resulted in information on hotspot spreading. Availability of information monitoring the distribution of hotspots latest rapid, precise and accurate can improve the remote sensing application to support the management of forest resources and establish a monitoring system that is accountable and can be a reference in the organization of activities of forest fire control and land at the same time participate in managing, maintaining safety as well as the preservation of IndonesiaÃ¢â‚¬â„¢s natural resources is sustainable. Given the importance of information and communication in disaster crisis management, efforts to facilitate the implementation of dissemination of hotspots distribution information to the wider community should properly be realized. One application is to develop a Web-based dissemination system Geographic Information System with Geonode application. The method used in this research is a prototype with open technology. Geonode can integrate that information to the layers with web mapping systems and the internet. The opensource geoportal system is built, the result of a combination of Django framework and Python programming language that is capable of providing dynamic spatial visualization interactively and connected to other electronic information networks. This Dissemination System can be used for decision makers in preparation of planning, development, monitoring, and response to an emergency disaster of forest and land fires in Indonesia, as well as a reference in the field of innovative technology and application of Geospatial information.Keyword:Ã‚Â hotspots, forest fires,Ã‚Â emergency response, Geonode,Ã‚Â dissemination,Ã‚Â web applicationsÃ‚Â Ã‚Â ABSTRAKPusat Pemanfaatan Pengideraan Jauh-LAPAN telah menghasilkan informasi sebaran titik panas. Ketersediaan informasi pemantauan sebaran titik panas terkini yang cepat, tepat dan akurat dapat meningkatkan pemanfaatan penginderaan jauh untuk mendukung pengelolaan sumber daya kehutanan dan membangun sistem pemantauan yang akuntabel dan dapat menjadi acuan dalam penyelenggaraan kegiatan pengendalian kebakaran hutan dan lahan sekaligus ikut serta dalam pengelolaan, menjaga keselamatan serta kelestarian sumber daya alam Indonesia yang berkelanjutan. Mengingat pentingnya informasi dan komunikasi dalam penanggulangan krisis akibat Ã‚Â bencana, maka upaya memudahkan pelaksanaan penyebarluasan informasi sebaran titik panas masyarakat luas dengan baik perlu diwujudkan. Salah satu pengaplikasiannya adalah dengan mengembangkan sistem diseminasi berbasis Web Sistem Informasi Geografis dengan aplikasi Geonode. Metode yang digunakan dalam penelitian ini adalah purwarupa dengan teknologi terbuka. Geonode dapat mengintegrasikan informasi tersebut dalam layer-layerÃ‚Â sistem pemetaan webÃ‚Â dan internet. Geonode merupakan sebuah sistem geoportal opensource gabungan antaran frameworkÃ‚Â Django dan bahasa pemograman Python yang mampu menyajikan visualisasi spasial dinamis secara interaktif dan terhubung ke jaringan informasi elektronik lainnya. Sistem diseminasi ini dapat dipakai untuk pengambilan keputusan dalam persiapan perencanaan, pembangunan, pengawasan, dan respon terhadap keadaan darurat bencana kebakaran hutan dan lahan di Indonesia, serta sebagai referensi dibidang teknologi inovatif dan penerapan informasi Geopasial.Kata kunci: titik panas, kebakaran hutan, tanggap darurat, Geonode, diseminasi, aplikasi webÃ‚Â Ã‚Â